FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN BUAH PISANG BERMEREK DAN TANPA MEREK - Herwina, Herdina; Nurhadi, Eko; Amir, Indra Tjahaja (Berkala Ilmiah AGRIDEVINA, 2020)
Consumer perspective on a product brand is important for the sustainability of products in the market, including banana. In this modern era, many people choose to buy fruit because of their high lifestyle and prestige. Therefore, it is necessary to conduct research to determine the level of consumer loyalty to the buying of branded and unbranded banana and to analyze the factors that influence the buying decision of branded and unbranded banana. The research was conducted in the Puncak Permai Surabaya modern market with 30 sample of branded banana consumer and 30 sample of unbranded banana consumer. The sampling technique uses non-probability sampling, the type of non-probability sampling used is accidental sampling. This research method uses a online questionnaire distributed via instagram and whatsapp. The data analysis used multiple linier regression analysis and consumner loyalty analysis. The results showed that there were 56,3% loyal branded banana consumers and 44% loyal unbranded banana consumers. On other side, the factors that significantly influence of banana buying decision are personal and psychological factors, while the income has a negative effect on the banana buying decision. DOI : https://doi.org/10.33005/adv.v9i2.2458